Vitiligo and pregnancy: How do each affect the other? - Abdel Mohsen Mohamed Ahmed Abdel Hafez; Karim A.M. Ahmed; Pang, Nicholas Tze Ping; Dg Marshita Pg Baharuddin; Win, Win Than; Fairrul Kadir; Mohammad Saffree Jeffree; Firdaus Hayati (Elsevier Ltd, 2021)
Vitiligo is one of the dermatomes affecting the melanocytes resulting in their destruction and subsequent patchy depigmentation of the skin. It is postulated to occur due to an autoimmune problem. Despite being a disease with limited systemic involvement and lack of mortality, it has a severe psychological impact. It may have a powerfully negative effect on a patient’s quality of life. The relationship between vitiligo and pregnancy is not widely acknowledged. It may be associated with adverse pregnancy outcomes such as recurrent miscarriage, prematurity, intrauterine growth retardation and pre-eclampsia. Herein, this review describes the disease’s adverse effects on pregnancy outcomes and the influence of pregnancy itself on the clinical evolution and prognosis of vitiligo.